Psychotic-like experiences with cannabis use predict cannabis cessation and desire to quit: a cannabis discontinuation hypothesis. Issue 1 (23rd March 2018) - Sami, Musa; Notley, Caitlin; Kouimtsidis, Christos; Lynskey, Michael; Bhattacharyya, Sagnik
Abstract: Background: Evidence suggests that cannabis-induced psychotic-like experiences may be a marker of psychosis proneness. The effect of such experiences on cannabis use has not systematically been examined. Methods: We undertook a mixed-methods online survey of 1231 cannabis users (including 926 continued users) using the Cannabis Experiences Questionnaire. We examined the effect of psychotic-like and pleasurable experiences on cessation of cannabis and intention to quit. Socio-demographic variables, cannabis use parameters and substance misuse history were included as covariates. Free-text data explored subjective reasons for changes in use. Results: Cessation of cannabis use was associated with greater psychotic-like experiences [ p < 0.001, Exp(B) 1.262, 95% confidence interval (CI) 1.179–1.351], whilst continued cannabis users were more likely to report pleasurable experiences [ p < 0.001, Exp(B) 0.717, 95% CI 0.662–0.776]. Intention to quit cannabis in continued users was associated with greater psychotic-like experiences [ p < 0.003, Exp(B) 1.131, 95% CI 1.044–1.225], whilst intention to not quit was significantly associated with increased pleasurable experiences [ p < 0.015, Exp(B) 0.892, 95% CI 0.814–0.978]. Whereas former users clearly ascribed cessation to negative experiences, continued users who expressed intention to quit less readily ascribed the intention to negative experiences. Conclusions: Elucidation of psychotic-like experiences may form the basis of a therapeutic intervention for those who wish to quit. Cessation in those with cannabis-induced psychotomimetic experiences may offset the risk for the development of a psychotic disorder, in this higher risk group.